Recommendations of the Polish Group of Experts for HCV for the treatment of hepatitis C in 2020 - Halota, Waldemar; Flisiak, Robert; Juszczyk, Jacek; Małkowski, Piotr; Pawłowska, Małgorzata; Simon, Krzysztof; Tomasiewicz, Krzysztof (Clinical and Experimental Hepatology, 2020)
The recommendations set out the principles of diagnosis and treatment of hepatitis C virus (HCV) infections according to the most recent knowledge. The main goal of therapy for HCV infection is to eliminate the virus from the body, which consequently leads to arrest of progress or regression of changes in the liver. Current version of the recommendations prioritise pangenotypic regimens and provide guidelines in special populations of patients, such as children, cirrhotics, human immunodeficiency virus (HIV) and hepatitis B virus (HBV) coinfected, those with renal failure, hepatic decompensation and non-responders to previous therapies.